Advances in food rheology and its applications - Ahmed, Jasim, 1966-; Ptaszek, Pawel; Basu, Santanu (Elsevier, Woodhead Publishing, 2017)
"This book presents in-depth and state-of-the-art coverage of the measurement and application of food rheology as a critical tool for food companies when characterizing ingredients and final products and predicting their performance and consumer acceptance"--Resumé vydavatele
Keywords: potravinářství; potraviny; reologie; food industry and trade; food; rheology; monografie; elektronické knihy; monographs; electronic books